The stability of grain yield in winter cereals in the drysubhumid pampas region (Semiárida, 2019)
Winter cereals are important in agrosystems of the drysubhumid Pampas region. Environmental factors such as rainfall and temperature dominant in the definition of grain yield, there is usually a great interaction with the genotype. The triticale (X Triticosecale Wittmack) and durum wheat (Triticum durum Desf.) may be alternatives to bread wheat (Triticum aestivum L.) to stabilize the grain yields of winter cereals. The study was conducted in the Faculty of Agronomy of UNLPam Experimental Field, located at 36º 46 'S and 64º 17' W, 210 m above sea level. The tests were conducted for eight years, which compared the three species, (five varieties of bread wheat, four of durum wheat and two of triticale), with two fertility conditions. The two triticale`s genotypes and bread wheat “Buck guaraní” had greater grain yield, while durum wheats showed average to low yields. The grain yield stability was not exclusive of one species, since triticale “Eronga 83”, bread wheat “ACA 601” and durum wheat “Ciccio” were stable, and bread wheat “Abate” and durum wheat “Buck cristal” were unstable. The CVi of Francis and Kannemberg and VEP of AMMI methods showed a good description of the clasification stability`s including all methods. The grain yield stability was not associated with higher yield potential.
Keywords: wheat; triticale; adaptation; genotype by environment interaction